POTENSI PENGEMBANGAN USAHA PETERNAKAN TERPADU DI ATAS LAHAN BEKAS TAMBANG PADA PT KPC KUTAI TIMUR - Joni Ariansyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The purpose of this study is to analyze and identify the resources and strength program of Peternakan Sapi Terpadu (PESAT ; integrated beef cattle farm) on the ex mining land at PT. KPC Kutai Timur. The experiment was conducted in September 2013 until the end of 2015. The study used qualitative methods, the survey through a case study on the program. Data was analyzed descriptively to explain in detail each of the resources and strengths of the program. The results showed that the resources and the strength of the mining company in Indonesia, especially by PT. KPC Kutai Timur is a strong capital in order to realize an alternative program or utilization of reclaimed mined land in Kutai Timur..